Extension Delivery System in a Layer and Swine-Based Farming Community: The Case of San Jose, Batangas - Rowena T. Baconguis (Philippine Institute for Development Studies (PIDS), 2007)
Public agricultural extension systems face increasing pressure resulting from diverse demands for services coupled with problems in declining funds. This study explores the role of a municipal agricultural extension system in the development of a robust agriculture-based municipality and their possible thrusts in helping achieve the country's bid for agricultural modernization. San Jose, Batangas is a layer and swine-led economy. Sandwiched between Batangas and Lipa City, San Jose is easily accessible to investors and traders. The phenomenal growth of the layer and swine industry is largely attributed to increased local demand and adoption of technological innovations in breeding and nutritional management practices encouraged by private suppliers of vaccines and feeds and feed millers who provide extension and credit terms. With the active participation of private extension providers, government extension system needs to improve its partnership with private and nongovernment extension providers and reevaluate its financing scheme to address negative externalities and equity concerns. The lack of a common vision among the key players in the government and the absence of knowledge management plan impair the impact of the government agricultural extension systems. Partnerships and good management practices remain as major areas for improvement.
Keywords: 330; decentralization; knowledge management; pluralistic extension; toll goods; Schweinehaltung; Geflügelhaltung; Landwirtschaftliche Entwicklung; Philippinen